Hubungan Latihan Menari Kelana Gaya Surakarta Dengan Indeks Massa Tubuh Pada Remaja Putri 15 - 17 Tahun Di SMK Negeri 8 Surakarta - Rosmawati, Ema Nur; , Isnaini Herawati, SSt. FT, M. Sc; , Sugiono S.Fis.MH.Kes (2016)
Background: Kelana Surakarta dance is a dance style that uses motion as the media said. Dance movements were refined and given an aesthetic element. In dancing, dancer always pay attention to their body shape in order to maximaze performance. Leaner body shape is considered to facilities the move. Purpose: To determine the relationship between the Kelana dance Surakarta style with a body mass index of young women aged 15-17 years. Benefit of aresearch : As the information for the dancer traditional, that the form of the slim needed in dance. With a body sleek, can simplify the dancer in move. Research Methods: The study was observational with cross sectional approach. The sampling technique used random sampling, as many as 55 respondents. Measuring instrument studies using the scale and measurement height. Statistical test used was chi-square. Result of research: Statistically of body mass index level of young women aged 15-17 years showed a p-value of 0.013 or probability (significance) < 0.05. Conclusion: There is a relationship between the Kelana dance exercise Surakarta style with a body mass index of young women aged 15-17 years.